Psychological support of young sportsmen in powerlifting and weightlifting - A. N. Berestyanaya; S. N. Filippova; A. N. Kornilov; A. P. Oreshkov; V. V. Gorelik (National Electronic Information Consortium (NEICON), 2023)
The article is a research into psychological and pedagogic support of sportsmen aged 18-25 years old, with taking into account the gender factor, at the stages of training with the strength exercises. It states methods of psychical reserves mobilization of different psychophysical types of sportsmen, aimed at training process efficiency increase in order to reach high results during competitions.Introduction. The article is based at the methodic of classical development of sportsmen's strength abilities in powerlifting in composition with psychological methods of psychological and pedagogic support (PPS) for increasing of reliability and successfulness of pre-competition training. PPS is considered to be a combination of targets, media, methods and circumstances of planning, realization and control of the process of formation, activation and optimization of sportsmen's psychological processes, at the stages of preparing for competitions and participating in them. Research target. Theoretical elaboration and experimental substantiation of the methodic of PPS training preparation for the competitions when going in for powerlifting and weightlifting.Materials and methods. The method of control test, pedagogic experiment (PE), fitness tests, anthropometrical methods, psychological development of personality methods, mathematical statistics methods. The research was being performed during five weeks (2020-02-01-2020-03-15). During the pedagogical experiment (PE), strength trainings were based at five-week cycle by B.I. Sheyko, which is equal to one pre-competition mesocycle. Sportsmen aged 18-25 years old formed two groups of 20 persons each: control group (CG) and experimental group (EG), divided [inside] by the gender factor. CG and EG were training with the classical powerlifting methodic, in EG it was supplemented with psychological processes optimization methods.The methodic of PPS preparation for a competition included: learning of goal-setting, forming of readiness for competitions, learning of coping, activation of motivation processes, increase of self-control and of psychoregulation of behavior and sport activity.Results. The authors elaborated five-week mesocycle (medium cycle) of training for powerlifters aged 18-25 years old. The forming impact of the complex of PPS methods in EG caused certain growth of strength results in EG at the end of PE: each of CG sportswomen lifted 142.5 kg in the sum of three-lift, CG sportsmen - 215 kg. In EG the result of sportswomen is 190 kg, the result of sportsmen is 250 kg. The growth, when comparing EG and CG, was 57.5 kg for sportswomen and 35 kg for sportsmen in favour of RG with PPS. Psychophysical types of young powerlifters, who need psychological and pedagogic support, were identified, recovery measures for psychological preparation were proposed.Conclusion. PPS in the complex with strength trainings caused certain growth of strength indexes of powerlifters aged 18-25 years old, with taking into account the gender factor. Strength indexes of girls progressed 1,8-2 times more significantly, than of men. When performing PPS, they wust take into account the gender specifics of powerlifters, attached to different impact of psychological preparation methods on boys and girls.